Preservation of Lycopersicum esculentum (Tomatoes) with Extracts of Annona muricata (Soursop) and Hibiscus sabdariffa (Roselle Plant) - Temitope T. Banjo; Omowunmi R. Oluwole; Victoria I. Nzei (Tropical Life Sciences Research, 2022)
Tomatoes are very important vegetable crops in the world but with a perishable nature. Due to its highly perishable nature, various methods have been investigated to increase its shelf life while still preserving its qualities. Therefore, this study investigated the potentials of the parts of Annona muricata and the calyces of Hibiscus sabdariffa in the preservation of tomato fruits. Tomato fruits were washed and treated with powdered, aqueous and ethanolic extracts of the leaves, seeds, bark of the Annona muricata and calyces of Hibiscus sabdariffa at different concentrations of 3%, 5%, 6%, 9% and 12% w/v. The tomato fruits were placed in well-aerated baskets for a period of 35 days during which organoleptic and microbial analysis were carried out. The different treatments with Annona muricata and Hibiscus sabdariffa had significant effects on the preservation of the tomato fruits at p < 0.05. The leaves of Annona muricata proved most effective preserving up to 50% of the tomatoes after the monitoring period. Moreover, 6% (w/v) of the aqueous extract of the leaves of Annona muricata resulted in a preservation rate of 75% of the tomato fruits. The spoilage microorganisms isolated from the tomato fruits are Candida krusei, Candida sp., Bacillus subtilis and Bacillus sp. The results of this research carried out shows that the extracts of Annona muricata and Hibiscus sabdariffa had significant preservative activities on the tomato fruits (p < 0.05), thus minimising wastes and economic loss to the farmers and country in general.